2012
DOI: 10.1183/09031936.00109112
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis is related to lung volumes and airflow limitation: a cross-sectional study

Abstract: This study aimed to assess the potential association of periodontal diseases with lung volumes and airflow limitation in a general adult population.Based on a representative population sample of the Study of Health in Pomerania (SHIP), 1463 subjects aged 25-86 years were included. Periodontal status was assessed by clinical attachment loss (CAL), probing depth and number of missing teeth. Lung function was measured using spirometry, body plethysmography and diffusing capacity of the lung for carbon monoxide. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 59 publications
(102 reference statements)
5
34
0
1
Order By: Relevance
“…OHI‐S indicates the level of oral hygiene, whereas CAL is the major periodontal clinical parameter indicating the severity of chronic periodontitis. Furthermore, previous studies have reported a relationship between the respiratory function index (FEV1%) and the degree of periodontal inflammation …”
Section: Discussionmentioning
confidence: 99%
“…OHI‐S indicates the level of oral hygiene, whereas CAL is the major periodontal clinical parameter indicating the severity of chronic periodontitis. Furthermore, previous studies have reported a relationship between the respiratory function index (FEV1%) and the degree of periodontal inflammation …”
Section: Discussionmentioning
confidence: 99%
“…The COPD patients in Prasanna’s study were also noted to belong to a lower income group, were more illiterate, and were of a lower socioeconomic status regardless of periodontal status 40. Holtfreter et al found that patients with higher indices of periodontitis were less well educated and more often current smokers and had higher levels of systemic inflammation and worse lung function 101. All these studies indicate significant confounders that likely impact on results published to date even though Bhavsar et al did not find any differences in socioeconomic status or educational qualifications between their COPD cohort and control groups 95…”
Section: Socioeconomic Statusmentioning
confidence: 93%
“…However, some authors used pre-bronchodilator spirometry,107 which could lead to an overestimation of the prevalence of COPD, others report lung function measurements but not whether pre- or post-bronchodilation,40,98 and one study failed to mention how COPD was confirmed 99. A German prospective study used body plethysmography to determine lung function,101 whereas Shen et al used International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes that do not provide details of how the diagnosis was established 33…”
Section: Potential Limitations Of These Studiesmentioning
confidence: 99%
“…32 Although no data exists to date that compared simultaneously microbiota of the periodontal pocket and the bronchial compartment, several recent studies have shown an association of periodontal health and airflow limitation. 12,16,33 Although not statistically significant, it is an interesting finding of the current study that in subjects with key pathogenic marker species exhibited more often amounts of activated MMP8 (>40 ng/ml) as compared to subjects who did not harbor these bacteria in the lung. MMP8 has been shown to be elevated in bronchoalveolar lavage fluid under different inflammatory circumstances of the lung such as ventilator induced lung injury 34 or bacterial pneumonia.…”
Section: Discussionmentioning
confidence: 68%
“…8 The microorganisms detected in the subgingival plaque of affected patients predominantly consist of Gram-negative fastidious anaerobic rods. 9 Periodontal inflammation has been associated with several lung diseases such as COPD, 10e15 airflow limitation 16 or pneumonia. 17 In a pilot study we were able to detect periodontal pathogens in the lungs of lung transplant recipients in spite of the frequent use of antibiotics in this specific population.…”
Section: Introductionmentioning
confidence: 99%